Phosphorus removal from aqueos solutin using aerated high calcium low ferum steel slag filter - Kamarudin, Siti Nur Aininabihah; Hamdan, Rafidah (Penerbit UTHM, 2020)
Phosphorus is a culprit nutrient in accelerating of eutrophication in natural surface waters. Eutrophication is a pollution that cause from an overabundance of nutrient occurs in the lake or river which is the water resource for the human. It is vary alarming as it will increased purification cost and also pose lethal effect of algal toxins in drinking water. The effect from that it reduces the amount of oxygen because the organism also needs oxygen for their life. The bloom of organism will cover the surfaces of water and it will prevent sunlight from entering the water [1].